Oral immunization of a non-recombinant Lactococcus lactis surface displaying influenza hemagglutinin 1 (HA1) induces mucosal immunity in mice - Jee, Pui-Fong; Tiong, Vunjia; Shu, Meng-Hooi; Khoo, Jing-Jing; Wong, Won Fen; Abdul Rahim, Raha; AbuBakar, Sazaly; Chang, Li-Yen (PloS one, 2017)
Mucosal immunization of influenza vaccine is potentially an effective approach for the prevention and control of influenza. The objective of the present study was to evaluate the ability of oral immunization with a non-recombinant Lactococcus lactis displaying HA1/L/AcmA recombinant protein, LL-HA1/L/AcmA, to induce mucosal immune responses and to accord protection against influenza virus infection in mice. The LL-HA1/L/AcmA was orally administered into mice and the immune response was evaluated. Mice immunized with LL-HA1/L/AcmA developed detectable specific sIgA in faecal extract, small intestine wash, BAL fluid and nasal fluid. The results obtained demonstrated that oral immunization of mice with LL-HA1/L/AcmA elicited mucosal immunity in both the gastrointestinal tract and the respiratory tract. The protective efficacy of LL-HA1/L/AcmA in immunized mice against a lethal dose challenge with influenza virus was also assessed. Upon challenge, the non-immunized group of mice showed high susceptibility to influenza virus infection. In contrast, 7/8 of mice orally immunized with LL-HA1/L/AcmA survived. In conclusion, oral administration of LL-HA1/L/AcmA in mice induced mucosal immunity and most importantly, provided protection against lethal influenza virus challenge. These results highlight the potential application of L. lactis as a platform for delivery of influenza virus vaccine.